2017
DOI: 10.1039/c7ra06471c
|View full text |Cite
|
Sign up to set email alerts
|

Design of a multifunctional vanadium pentoxide/polymer biocomposite for implant-coating applications

Abstract: In this study we designed a multifunctional implant coating by exploiting the properties of V2O5, i.e. the antibacterial activity via myeloperoxidase-like catalytic activity and the bioactivity of low concentrations of vanadate ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…For example, due to an increase in bacteria-material contacts, surfaces with MgO micro rods could have faster bacterial elimination than commercially available MgO. [47] As such, implant coating with laser-induced conformal 3D porous structures was found to interfere with bacterial shape, and in turn, their adhesion and proliferation. [48] This inhibited bacterial adhesion relies greatly on bacterial-surface contact, suggesting that a surface with hierarchical topographies could deliver more anti-adhesive and/or initial killing effects on bacteria, as evidenced by a nanoimprinted PLLA/Si, Sr-nHA surface.…”
Section: Available Contact-adhesion Pointsmentioning
confidence: 99%
“…For example, due to an increase in bacteria-material contacts, surfaces with MgO micro rods could have faster bacterial elimination than commercially available MgO. [47] As such, implant coating with laser-induced conformal 3D porous structures was found to interfere with bacterial shape, and in turn, their adhesion and proliferation. [48] This inhibited bacterial adhesion relies greatly on bacterial-surface contact, suggesting that a surface with hierarchical topographies could deliver more anti-adhesive and/or initial killing effects on bacteria, as evidenced by a nanoimprinted PLLA/Si, Sr-nHA surface.…”
Section: Available Contact-adhesion Pointsmentioning
confidence: 99%
“…On the other hand, the PDPA processed in acidic medium in presence of V 2 O 5 particles failed to enwrap the inorganic phase of V 2 O 5 , which may be due to its complete leaching during the polymerization of DPA resulting in the formation of fully porous structure of PDPA. The morphology changed from rod to fully porous granular structure with the change in reaction medium from aqueous to acidic can be explained by the fact that V 2 O 5 is soluble in acidic medium that make the DPA monomer more hydrophilic, while the insolubility of V 2 O 5 in pure aqueous (H 2 O) medium provides hydrophobic nature to DPA [25,26]. Hence, the hydrophilic nature of DPA monomer in 1 M HCl medium reduces the repulsion between the charged hydrophilic groups that destroyed the morphology of V 2 O 5 resulting in irregular granules of PDPA [18].…”
Section: Sem-edsmentioning
confidence: 99%
“…The first mechanism was reported by Anicic et al in 2017 91 . They showed that vanadia nanostructures mimic the myeloperoxidase-like catalytic activity of human neutrophils.…”
Section: Vanadium Oxidementioning
confidence: 97%
“…At low concentrations, ions also help in tissue repair and improve the bone formation rate in vivo. In contrast, a high concentration of vanadate ions is toxic to human cells 91 . Hence, control and sustained release of vanadate ions are key to leverage the abovesaid beneficial properties.…”
Section: Vanadium Oxidementioning
confidence: 99%